Barriers to accessing health care of older Chinese immigrants in Canada: a scoping review - Zhu, Change; Song, Baoxiang; Walsh, Christine A.; Ekoh, Prince Chiagozie; Qiao, Xuebin; Xu, Aijun (Frontiers in Public Health, 2024)
BackgroundThis scoping review aims to examine the extant literature and summarize findings related to barriers to accessing health care faced by older Chinese immigrants in Canada.MethodsWe conducted a search of electronic databases for peer-reviewed articles using a comprehensive set of keywords without limiting the search to a specific time period. To be included in our review, articles had to meet the following criteria: (a) published in a peer-reviewed journal, (b) written in English, (c) provide a clear description of the methods used, and (d) respond to our research question, which focuses on identifying barriers to accessing healthcare for older Chinese immigrants living in Canada.ResultsFifteen papers were selected based on the criteria, and five main barriers were identified, which are ranked in descending order according to the number of times they were mentioned: culture and health beliefs (N = 13), language and communication (N = 7), structural and circumstances (N = 2), health literacy and information (N = 2), and demographic, social, and economic factors (N = 2).ConclusionsThe issue of accessing healthcare for older Chinese immigrants in Canada is complex, as it involves multiple aspects that are relevant to both patients and healthcare providers. Our research findings suggest that the culturally and linguistically sensitive education programs, inter-sectoral coordination, and social support should be improved for older Chinese immigrants and those of other ethnic backgrounds.